Sociology of religion : overview and analysis of contemporary religion - Day, Abby, 1956- (Abingdon, Oxon ; New York : Routledge, 2020)
'The first sociology of religion textbook to begin the task of diversifying and decolonizing the study of religion, Sociology of Religion develops a sociological frame that draws together the personal, political and public, showing how religion - its origins, development and changes - is understood as a social institution, influenced by and influencing wider social structures. Organized along sociological structures and themes, the book works with examples from a variety of religious traditions and regions rather than focusing in depth on a selection, and foregrounds cultural practice-based understandings of religion. It is therefore a textbook about'religion', not'religions', that explores the relationship of religion with gender and sexuality, crime and violence, generations, politics and media,'race', ethnicity and social class, disease and disability - highlighting the position of religion in social justice and equality. Each chapter of this book is framed around concrete case studies from a variety of Western and non-Western religious traditions. Students will benefit from thinking about the discipline across a range of geographical and religious contexts. The book includes features designed to engage and inspire students
Includes bibliographical references and index.
Buku bacaan asas Fakulti Pengajian Islam sesi 2022/2023.
Keywords: Religion and sociology -- Textbooks